Diffusion tensor imaging for the assessment of upper motor neuron integrity in ALS - Graham, J M; Papadakis, N; Evans, J; Widjaja, E; Romanowski, C A J; Paley, M N J; Wallis, L I; Wilkinson, I D; Shaw, P J; Griffiths, P D (Neurology, 2004)
High angular resolution diffusion tensor imaging (HARD) is an MRI technique that exploits the mobility of water molecules to yield maps of structural order and directionality of white matter tracts with greater precision than six-direction diffusion tensor imaging (DTI) schemes. To assess whether HARD is more sensitive than conventional MRI or neurologic assessment in detecting the upper motor neuron (UMN) pathology of patients with ALS. Twenty-five patients with definite UMN clinical signs and 23 healthy volunteers underwent conventional MRI. HARD datasets were collected from a subset of these participants plus four patients with isolated lower motor neuron (LMN) signs. ALS symptom severity was assessed by a neurologist, the conventional MR images were reviewed by neuroradiologists, and the DTI maps were subject to quantitative region of interest analysis. Motor cortex hypointensity on T2-weighted images and corona radiata hyperintensity on proton density-weighted images distinguished patients with UMN involvement from volunteers with 100% specificity, but only 20% sensitivity. Fractional anisotropy (FA) was reduced in the posterior limb of the internal capsule in patients with UMN involvement compared to volunteers. A FA threshold value with a sensitivity of 95% to detect patients with ALS (including those with isolated LMN signs) had a specificity of 71%. High angular resolution diffusion tensor imaging may be more sensitive than conventional MRI or neurologic assessment to the upper motor neuron (UMN) pathology of ALS, but it lacks the specificity required of a diagnostic marker. Instead, it is potentially useful as a quantitative tool for monitoring the progression of UMN pathology.